1983
DOI: 10.1254/jjp.33.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high potassium depolarization, carbachol and oxytocin on the lanthanum-resistant 45Ca fraction in rat myometrium.

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…On the other hand, it has been reported that the high K+ induced contraction in rat uterus is under the influence of estrogen and progesteron (Ishii et al 1986, Takayama et al 1986, Uruno et al 1983. We have already reported that the decrease of the developed tension in isosmotically substituted high K+/Na+deficient solution in rat uterus of estrus phase is probably due to the cell swelling (Kamizaki et al 1988).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, it has been reported that the high K+ induced contraction in rat uterus is under the influence of estrogen and progesteron (Ishii et al 1986, Takayama et al 1986, Uruno et al 1983. We have already reported that the decrease of the developed tension in isosmotically substituted high K+/Na+deficient solution in rat uterus of estrus phase is probably due to the cell swelling (Kamizaki et al 1988).…”
Section: Introductionmentioning
confidence: 97%